2009
DOI: 10.1097/acm.0b013e3181b17e55
|View full text |Cite|
|
Sign up to set email alerts
|

The Devil is in the Third Year: A Longitudinal Study of Erosion of Empathy in Medical School

Abstract: It is concluded that a significant decline in empathy occurs during the third year of medical school. It is ironic that the erosion of empathy occurs during a time when the curriculum is shifting toward patient-care activities; this is when empathy is most essential. Implications for retaining and enhancing empathy are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

92
1,088
22
123

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,322 publications
(1,394 citation statements)
references
References 36 publications
92
1,088
22
123
Order By: Relevance
“…Several studies [14] have investigated the evolution of empathy scores for medical students throughout their education in medicine, and reported a significant empathy decline from the beginning to the end of their education. This study attempted to show whether incoming medical students were incline to reveal significant differences in empathy levels according to the population of reference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies [14] have investigated the evolution of empathy scores for medical students throughout their education in medicine, and reported a significant empathy decline from the beginning to the end of their education. This study attempted to show whether incoming medical students were incline to reveal significant differences in empathy levels according to the population of reference.…”
Section: Discussionmentioning
confidence: 99%
“…However, several researchers and one of our recent research reported a striking and progressive decline of empathy levels among medical students over time of education [1,2]. Several interpretations were proposed: changes from idealism to realism [3]; overusing of technologies [4]; promotion of emotional detachment, affective distance and clinical neutrality [5]. Therefore, psychological or environmental factors and personality influence the decline of empathy among medical students.…”
Section: Introductionmentioning
confidence: 99%
“…The negative view of empathy in medicine Many have noted and discussed the difficulty of current medical students and professionals to empathize with patients (Eikeland et al 2014;Hojat et al 2004Hojat et al , 2009Suchman et al 1997;Tavakol et al 2012;Ward et al 2012). Studies have made use of multiple tools to measure this decline in empathy, including the Jefferson Scale of Physician Empathy (henceforth JSPE), the Interpersonal Reactivity Index, and questionnaires (Hojat et al 2004(Hojat et al , pp.…”
Section: A Problematic Lack Of Empathymentioning
confidence: 99%
“…After a long hiatus, the topic of empathy is now being revisited as something that is essential to good medical practice. According to a few recent studies, the physician's ability to empathize with patients is weakened during medical training, and this weakened ability can lead to a serious deficiency in patient care (Hojat et al 2004(Hojat et al , 2009Eikeland et al 2014;Suchman et al 1997;Tavakol et al 2012;Ward et al 2012). In order to improve patient care, these studies also argue that empathy is a skill that should be fostered in a student's initial medical training.…”
mentioning
confidence: 99%
“…However, a particular understanding within medical ethics literature, Bdefined empathy in the context of medical education and patient care as a predominantly cognitive (as opposed to affective or emotional) attribute that involves an understanding (as opposed to feeling) of patients' experiences, concerns, and perspectives combined with a capacity to communicate this understanding^ (Hojat 2009). Such an explication of empathy is helpful in the sense that it allows for recognition of the fact that being emotionally tied to one's patient can also cripple a physician's ability to do her job.…”
Section: The Formation Of Doctorsmentioning
confidence: 99%